PENERAPAN SMART BOX WARISAN BUDAYA JAWA TIMUR UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS V SDN 01 KLEGEN - Alfian Vidianingrum; Candra Dewi; Nurul Wiji Astuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the learning outcomes of fifth-grade students at SDN 01 Klegen in the subject of IPAS (Natural and Social Sciences), specifically the material on Local Cultural Heritage, through the implementation of the Smartbox media on East Java Cultural Heritage. The background of this research is the low learning outcomes of students, which are caused by a lack of contextual learning, limited use of media, and the dominance of a teacher-centered approach. This research employs the Classroom Action Research (CAR) method, consisting of two cycles. The research subjects are 28 fifth-grade students. Data collection techniques include tests, observations, and documentation, with data analysis conducted using descriptive quantitative methods. The results show an improvement in learning outcomes after the implementation of the Smartbox media. The average score increased from 60 in the pre-cycle to 71.60 in Cycle 1, and reached 81.67 in Cycle 2. The percentage of students who achieved learning mastery improved from 36% (pre-cycle) to 46% (Cycle 1) and 89% (Cycle 2). The implementation of Smartbox proved to enhance students' understanding of abstract IPAS concepts by combining visual elements, interactive activities, and the use of digital media. Thus, the Smartbox media on East Java Cultural Heritage is effective in improving IPAS learning outcomes for elementary school students on the material of Local Cultural Heritage.